Closing the door in front of a torrential mitral regurgitation. Issue 10 (20th September 2022) - Mansour, Mohamad Jihad; Natalis, Alexandre; Masson, Jean‐Bernard; Potvin, Jeannot; Romanelli, Giovanni
Abstract: Background: Treatment of symptomatic severe mitral regurgitation (MR) is challenging in patients who are not candidates for surgical intervention. Case Description: We report the case of a 64‐year‐old female with multiple comorbidities who was found to have severe MR due to a large mitral valve non coaptation. Conclusions: In this case report, we show the potential of transcatheter edge‐to‐edge mitral valve repair using MitraClip for the treatment of torrential MR due to a large mitral valve non‐coaptation in a patient with no prior history of coronary artery disease and in whom surgical intervention was not an option.